Iranian nursing applicants' perception of the nursing profession: A qualitative study - Vahid Zamanzadeh; Akram Ghahramanian; Leila Valizadeh; Farzaneh Bagheriyeh (Wiley, 2023)
Abstract Aim This study was conducted to describe the perceptions of nursing applicants about their chosen profession and to explore the factors which influenced their understanding. Design A qualitative study with a conventional content analysis design. Methods Participants were 19 nursing applicants enrolling in nursing schools in three provinces of western Iran. Data were collected using semi‐structured interviews. The content analysis of the interviews was done according to the steps proposed by Zhang and Wildemuth. Results The mean age of participants was 20 years (SD = 2.5), and 11 of them (57.9%) were females. Participants understood the nature of nursing work to encompass only a limited level of independence; they viewed it as a feminine profession, and as a job with spiritual rewards. The perceived content of nursing work included providing help and patient care in the hospital with a focus on performing procedural tasks. Applicants' perceptions of nurses' characteristics included strong physical endurance, communication skills, emotional strength and low intellectual skills. The professional status of nursing was perceived simultaneously as having high job security but limited potential for career advancement and professional growth. The factors reported to influence applicants' perceptions were related to the media, academic-career counsellors, personal factors, and family and friends.